Pengaruh Terapi Pijat Oksitosin Terhadap Kelancaran ASI pada Ibu Nifas di Wilayah Kerja Puskesmas M.Taha Bengkulu Selatan - Yulita Elvira Silviani; Desi Fitriani; Elma Fitri (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2023)
Baground: The coverage of infants who received exclusive breastfeeding at the M. Taha Health Center was 59.26%, the last of the 14 health centers in Bengkulu Selatan Regency, due to one of the reasons for the lack of milk production. Oxytocin massage is one solution to overcome the non-smooth milk production. Purpose: The purpose of this research is to study the effect of oxytocin massage therapy on the smoothness of breast milk in post partum’s women in the M. Taha Health Center, Bengkulu Selatan Regency. Method: This is research uses a pre-experimental with the One Group Pre-Test and Post Test Design Method. The population is all post partum’s women <24 hours in the working area of ??the M. Taha Health Center, Bengkulu Selatan Regency. Sampling used the Accidental Sampling technique, with a sample of 16 respondents. Data collection using interview techniques and oxytocin massage therapy treatment. Results: The results showed that from 16 respondents, the average value of the smoothness breast milk before the oxytocin massage treatment was 4.19 and the average value of the smoothness breast milk after the oxytocin massage treatment was 8.38. Conclusion: There is an effect of oxytocin massage therapy on the smoothness breast milk in post partum’s women in the Working Area of ??the M. Taha Health Center Bengkulu Selatan Regency. It is recommended to the Puskesmas that oxytocin massage therapy can be used as a permanent procedure as a post partum’s service at the Puskesmas and teach/socialize to mothers about oxytocin massage and its benefits for breast milk mothers.